2014
DOI: 10.1111/bju.12728
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and benign prostatic enlargement: a systematic review and meta-analysis

Abstract: Objective To summarise and meta‐analyse current literature on metabolic syndrome (MetS) and benign prostatic enlargement (BPE), focusing on all the components of MetS and their relationship with prostate volume, transitional zone volume, prostate‐specific antigen and urinary symptoms, as evidence suggests an association between MetS and lower urinary tract symptoms (LUTS) due to BPE. Methods An extensive PubMed and Scopus search was performed including the following keywords: ‘metabolic syndrome’, ‘diabetes’, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
167
3
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(192 citation statements)
references
References 55 publications
14
167
3
8
Order By: Relevance
“…Accumulating evidence suggests that BPH is particularly observed in men with diabetes mellitus and metabolic syndrome, although the pathogenetic mechanisms underlying these connections have not yet been completely clarified (Gacci et al, 2015). Recent studies reported higher rate of surgery for enlarged prostate or BPH in diabetes (Sidney et al, 1991;Sarma & Kellogg, 2009), and a low vitamin D status in two-thirds of patients with type 2 diabetes mellitus and in particular among diabetic patients with poor glycaemic control or longer diabetes durations.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that BPH is particularly observed in men with diabetes mellitus and metabolic syndrome, although the pathogenetic mechanisms underlying these connections have not yet been completely clarified (Gacci et al, 2015). Recent studies reported higher rate of surgery for enlarged prostate or BPH in diabetes (Sidney et al, 1991;Sarma & Kellogg, 2009), and a low vitamin D status in two-thirds of patients with type 2 diabetes mellitus and in particular among diabetic patients with poor glycaemic control or longer diabetes durations.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review and meta-analysis of eight studies involving 5403 patients, Gacci et al [21] suggested that the occurrence of metabolic syndrome in elderly men with a larger prostate could represent a major contributing factor in BPE progression. In ameta-regression analysis of the meta-analysis, the authors further suggested that obese, dyslipidemic (low serum HDL concentration in particular) and aged patients were more at risk of having metabolic syndrome as a determinant of their increased prostate size.…”
Section: Discussionmentioning
confidence: 99%
“…Наличие ме-таболического синдрома связано с достоверно боль-шим общим объемом предстательной железы и боль-шей медианой ежегодного прироста ее переходной зоны, а также с достоверно более высоким уровнем простатспецифического антигена в крови, который может считаться, по мнению ряда авторов, индексом простатического объема и критерием выраженности СНМП [55][56][57][58][59]. Сегодня ДГПЖ рассматривается как системное гормонально-метаболическое заболевание, в основе патогенеза которого лежат дислипидемия, хроническое воспаление и нарушение соотношения тестостерон/эстрадиол [60][61][62][63]. Низкий уровень тесто-стерона наблюдается как минимум у 1 из 5 больных ДГПЖ [64].…”
Section: эстрогены и мужская репродукцияunclassified